(untitled) (Journal of Engineering, 2021)
In the last decades, using mineral admixture in concrete became very necessary to improve concrete properties and reduce CO2 emissions associated with the cement production process. Subsequently, more sustainable concrete can be obtained. Ternary blended cement containing two different types of mineral admixture can achieve ambitious steps in this trend. In this research, the synergic effects of mineral admixtures in ternary blended cement and its effects on concrete fresh properties, strength, durability, and efficiency factors of mineral admixture in ternary blended cement, were reviewed. The main conclusion reached after reviewing many literature pieces is that the concrete with ternary blended cement, depending on types of mineral admixtures used, replacement percentages by weight of cement, and age of concrete, exhibited superior properties than with no mineral admixtures and corresponding binary blended cement concrete.